逻辑电路如图所示,F=0 的条件是( )。[img=132x153]17de8aa3ae23be4.jpg[/img]
A: ABC=110
B: ABC=111
C: ABC=001
D: ABC=000
A: ABC=110
B: ABC=111
C: ABC=001
D: ABC=000
A
举一反三
- 逻辑函数F=AB+BC,使F=0的输入ABC组合为 。 A: ABC=111 B: ABC=011 C: ABC=110 D: ABC=000
- 函数F=AB+BC,可以使F=1的输入ABC组合为( ) A: ABC=011 B: ABC=110 C: ABC=111 D: ABC=000 E: ABC=100 F: ABC=101 G: ABC=001
- 函数[img=87x16]17e440110f1e11a.jpg[/img],使[img=35x14]17e4401117ebf83.jpg[/img]的输入ABC组合为()。 A: ABC=000 B: ABC=010 C: ABC=101 D: ABC=110
- 函数F=AB+BC,使F=1的输入ABC组合为 A: ABC=100 B: ABC=110 C: ABC=011 D: ABC=000
- 函数F =AB +BC,使F=1的输入ABC 组合为 ( )。 A: ABC=000 B: ABC=010 C: ABC=101 D: ABC=110 E: ABC=011 F: ABC=100
内容
- 0
写出图示电路的逻辑表达式( )。[img=432x180]18031ee90d04dc1.jpg[/img] A: ABC’ B: ABC+B’ C: ABC’+B D: ABC
- 1
函数Y=AB+BC,使得Y=1的ABC组合为 A: ABC=110 B: ABC=101 C: ABC=111 D: ABC=011
- 2
函数Y=AB+BC,使Y=1的输入ABC组合为_________。 A: ABC=000 B: ABC=010 C: ABC=101 D: ABC=110
- 3
逻辑函数F=(A+BCʹ)(A+B),当ABC的取值为()时,F=0。 A: 000 B: 010 C: 100 D: 111
- 4
函数F(A,B,C)=AB+BC+AC,使F(A,B,C)=1的输入ABC组合为( ) A: 000 B: 010 C: 101 D: 110 E: 100 F: 001 G: 111